Pemanfaatan Podcast sebagai Media Dakwah di Era Digital - Erwan Efendi; Mhd. Habib Ansyahri Siregar; Dila Popyanti; M Ridwan (LPPM IAI Nasional Laa Roiba Bogor, 2024)
Podcasts are one of the many social media platforms that are growing rapidly. According to Fadilah (2017), podcasts are defined as online audio or video content that can be downloaded automatically to computers and smartphones for free or by subscription. This podcast content is a news source for internet-based radio broadcasts. The success of using podcast media for preaching can be seen from Ali Jaber and Habib Husain Jaffar Al Hadar. This research is descriptive qualitative research. The data source was obtained from searches of various podcast service provider sites and several previously existing related studies. Data was collected using documentation techniques and analyzed using the Huberman and Miles concept, namely through data reduction, data presentation, and drawing conclusions and verification. In 2005, podcasts began to gain popularity in Indonesia. On his weblog, Boy Avianto created his first podcast entitled